Iron deficiency among primary school children in Mosul City /Northern Iraq, a cross-section study - Nashwan Mustafa Al Hafidh; Elham Khattab Al-Jammas; Humam Zubeer (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the prevalence of iron deficiency among primary school students in an urban setting. Method: The descriptive, cross-sectional study was conducted from January to April 2019 in Mosul, Iraq, after approval from the ethics review committee of the College of Medicine, Nineveh University, Iraq, and comprised students aged 6-12 years who were part of the 2018-19 academic year at 4 public primary schools located along the two banks of Tigris River. Serum ferritin was measured in all the participants. Data wa analysed using Minitab 20. Results: Of the 827 subjects, 439(53%) were girls and 388(47%) were boys. The overall mean age was 8.5±0.057 years, with 558(67.5%) aged <10 years. The mean serum ferritin level was 8.05±6.43ng/ml, and 173(20.92%) subjects were found to iron-deficient. Among the iron-deficient students, 87(50.29%) had iron deficiency anaemia and 86(49.71%) had non-anaemic iron deficiency. Age and gender were significantly different between students with anaemic and non-anaemic iron deficiency (p<0.05). Within boys, significant difference was also noted in terms of body mass index-for-age values (p<0.05). Conclusion: One-fifth of the students were found to have iron deficiency. Plans to control iron deficiency among young children are essential. Key Words: Anaemia, Iron-Deficiency, Ferritins